Encephalic photoreception and phototactic response in the troglobiont Somalian blind cavefish Phreatichthys andruzzii - Tarttelin, Emma E.; Foulkes, Nicholas S. (The journal of experimental biology, 2012)
Skip to Next Section Many physiological and behavioural responses to changes in environmental lighting conditions are mediated by extraocular photoreceptors. Here we investigate encephalic photoreception in Phreatichthys andruzzii, a typical cave-dwelling fish showing an extreme phenotype with complete anophthalmy and a reduction in size of associated brain structures. We firstly identified two P. andruzzii photopigments, orthologues of rod opsin and exo-rod opsin. In vitro, both opsins serve as light-absorbing photopigments with λmax around 500 nm when reconstituted with an A1 chromophore. When corrected for the summed absorption from the skin and skull, the spectral sensitivity profiles shifted to longer wavelengths (rod opsin: 521 nm; exo-rod opsin: 520 nm). We next explored the involvement of both opsins in the negative phototaxis reported for this species. A comparison of the spectral sensitivity of the photophobic response with the putative A2 absorbance spectra corrected for skin/skull absorbance indicates that the A2 versions of either or both of these pigments could explain the observed behavioural spectral sensitivity.
Gesehen am 19.07.2017